2020
DOI: 10.1016/j.actatropica.2020.105414
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of circulation of West Nile virus in Culex pipiens mosquitoes and horses in Morocco

Abstract: West Nile virus (WNV) is one of the most widely distributed mosquito-borne viruses in the world. In North Africa, it causes human cases of meningoencephalitis with fatalities in Algeria and in Tunisia, whereas only horses were affected in Morocco. The aims of this study were to detect WNV in mosquitoes and to determine seroprevalence of WNV in Moroccan horses by the detection of IgG antibodies. A total of 1,455 mosquitoes belonging to four different species were grouped by collection site, date, and sex with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…More worryingly, the fact that OP and PYR resistances are already quite prevalent all over Morocco could impede mosquito control, while alternative insecticides are very limited. Beyond the nuisance and its impact on tourism, control failures could in this country lead to increased arbovirus transmission, as the WNV is actively circulating in Morocco, 58 which increases the risk of epizootics and epidemics. This risk is further increased by the prevalence of resistance, as a study recently showed that resistance alleles tend to increase Cx.…”
Section: Resultsmentioning
confidence: 99%
“…More worryingly, the fact that OP and PYR resistances are already quite prevalent all over Morocco could impede mosquito control, while alternative insecticides are very limited. Beyond the nuisance and its impact on tourism, control failures could in this country lead to increased arbovirus transmission, as the WNV is actively circulating in Morocco, 58 which increases the risk of epizootics and epidemics. This risk is further increased by the prevalence of resistance, as a study recently showed that resistance alleles tend to increase Cx.…”
Section: Resultsmentioning
confidence: 99%
“…All equids of volunteer owners were sampled in Northwest Senegal and every horse available without WNV vaccination was sampled in Southwestern Nigeria. Two recent studies conducted a survey of vectors alongside the seroprevalence of WNV in equids [ 26 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neutralization tests can resolve discrepancies that often occur with other assays due to cross-reactivity. Confirmatory neutralization tests were performed in most studies after initial screening with ELISA, microsphere immunoassay [ 26 ] or Western blot [ 31 ]. Neutralization tests performed included MNT, VNT and PRNT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that mosquitoes could be possible vectors for transmitting S. hominis while feeding on their host and that genetically these mecA + S. hominis isolates recovered from general public settings have not evolved much since ancient times (Hughes et al, 2016). Mosquitoes are vectors for viruses, protozoa and parasites that can spread and cause disease in humans and animals but currently, it is unreported if they can transfer and initiate bacterial infections (Torres-Guerrero et al, 2017;Assaid et al, 2020;Multini et al, 2020). The ENA isolates recovered from mosquitoes (As1, As2 and As3) were genetically related to an ENA isolate recovered from healthy human skin (UMB0272) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%